Survey Accuracy Analysis of a Hand-held Mobile LiDAR Device for Cultural Heritage Documentation - Chan, T.; Lichti, D.; Belton, D.; Klingseisen, B.; Helmholz, Petra (2016)
In this paper, the survey accuracy of a hand-held, GNSS-free mobile LiDAR device, the Zebedee, is studied by collecting measurements of several different geometric features in four different datasets. We use a new comprehensive accuracy assessment methodology based on geometric modelling which involves a geometric model of a prism/ pyramid for square structure. The point cloud accuracies of the features (planes, cylinders, catenaries, prisms and pyramids) were compared to that of a conventional survey-grade LiDAR system, the Leica ScanStation C10. The results suggested that the Zebedee accuracy is very comparable to the C10. For instance, the mean RMS error of plane fittings for the Zebedee is approximately 1.1 cm versus 0.6 cm for the C10. The estimated cylinder radii between the Zebedee and the C10 has only 1.4% difference in average, while the radii difference in prism/pyramid fitting is only 0.8%. As a result, the Zebedee LiDAR device is suitable for heritage mapping not only because it has high operation flexibility but also desired high accuracy.